IMPLEMENTASI PERMAINAN TRADISIONAL MODIFIKASI INDUSTRIAL ENGINEERING UNTUK MENINGKATKAN LITERASI NUMERASI DI SDN 173280 LOBU SIREGAR - Handayani, Rina; Sitompul, Sahat; Sihotang, Rinto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Numeracy literacy is a basic skill that is very important for elementary school students in facing the challenges of the 21st century. This research aims to improve the numeracy literacy of SD Negeri 173280 Lobu Siregar students through the implementation of traditional games modified with the concept of Industrial Engineering. The method used was a qualitative approach with a participatory action research design. The research subjects were 45 students of grades III-V of SD Negeri 173280 Lobu Siregar. The modified traditional games include Congklak Numeration, Jumping Rope Math, and Statistical Ladder Snakes developed with the principles of ergonomics, efficient work systems, and optimization of the learning process. Data were collected through pre-test and post-test of numeracy skills, observation of learning activities, and interviews with teachers and students. The results showed a significant increase in students' numeracy literacy skills by 35% from an average score of 65 to 88. Students also showed high enthusiasm in learning with participation rate reaching 95%. The implementation of Industrial Engineering concepts in game design proved effective in increasing the efficiency of the learning process and reducing the time to understand math concepts by 40%. This service program makes a real contribution to improving the quality of basic education and can be used as a replication model for other schools. ABSTRAK Literasi numerasi merupakan kemampuan dasar yang sangat penting bagi siswa sekolah dasar dalam menghadapi tantangan abad 21. Penelitian ini bertujuan untuk meningkatkan literasi numerasi siswa SD Negeri 173280 Lobu Siregar melalui implementasi permainan tradisional yang dimodifikasi dengan konsep Industrial Engineering. Metode yang digunakan adalah pendekatan kualitatif dengan desain penelitian tindakan partisipatif (Participatory Action Research). Subjek penelitian adalah 45 siswa kelas III-V SD Negeri 173280 Lobu Siregar. Permainan tradisional yang dimodifikasi meliputi Congklak Numerasi, Lompat Tali Matematika, dan Ular Tangga Statistik yang dikembangkan dengan prinsip-prinsip ergonomi, sistem kerja yang efisien, dan optimasi proses pembelajaran. Data dikumpulkan melalui pre-test dan post-test kemampuan numerasi, observasi aktivitas pembelajaran, dan wawancara dengan guru dan siswa. Hasil penelitian menunjukkan peningkatan signifikan kemampuan literasi numerasi siswa sebesar 35% dari skor rata-rata 65 menjadi 88. Siswa juga menunjukkan antusiasme yang tinggi dalam pembelajaran dengan tingkat partisipasi mencapai 95%. Implementasi konsep Industrial Engineering dalam desain permainan terbukti efektif meningkatkan efisiensi proses pembelajaran dan mengurangi waktu pemahaman konsep matematika hingga 40%. Program pengabdian ini memberikan kontribusi nyata dalam peningkatan kualitas pendidikan dasar dan dapat dijadikan model replikasi untuk sekolah-sekolah lain.